Anti-herpes simplex virus activity of extracts from the culinary herbs Ocimum sanctum L., Ocimum basilicum L. and Ocimum americanum L - Raenu Yucharoen (2018)
This study demonstrates anti-herpes simplex virus activity of dichloromethane and methanol extracts of Ocimum sanctum L., Ocimum basilicum L. and Ocimum americanum L. Green monkey kidney cells were protected from HSV-2 infection by the dichloromethane extract of O. americanum L. and the methanol extract of O. sanctum, with therapeutic indexes (TI) of 1.865 and 1.644, respectively, when the cells were treated before viral infection. Herpes simplex virus-2 (HSV-2) infection was inhibited during viral adsorption when the cells were treated with methanol extracts of O. americanum L., O. sanctum L. and O. basilicum L. with TI of 2.345, 2.473 and 1.563, respectively, whereas dichloromethane extracts of O. americanum L. and O. basilicum L. resulted in TI of 2.623 and 1.835, respectively. The methanol extract of O. americanum L. and the dichloromethane extract of O. basilicum L. inhibited HSV-1F with TI of 1.63 and 2.215, respectively, after viral adsorption. The inhibitory effects of extracts on HSV-2G, after viral adsorption, were quite high, for the dichloromethane extract of O. sanctum L. and the methanol extract of O. sanctum L. with TI of 10.003 and 29.395, respectively. The inhibitory effect of the O. americanum L. extract on HSV-1F and HSV-2 yield, after viral replication, was highest 30 h after treatment. The reduction of viral titers by 8.0 and 10.8 folds was observed when cells were treated with dichloromethane and methanol extracts of O. americanum L. Moreover, time-dependent virucidal effects of the extract on viral particles were demonstrated, since direct inhibition of both HSV-1F and HSV-2G was shown by a reduction in the amount of plaques by 100%, after treatment with the dichloromethane and methanol extracts of O. americanum L. Therefore, dichloromethane and methanol extracts of O. sanctum L., O. basilicum L. and O. americanum L. showed anti-HSV activities at various steps of the viral multiplication cycle. © 2011 Academic Journals.